2016
DOI: 10.1038/srep22070
|View full text |Cite|
|
Sign up to set email alerts
|

Hemoglobin induced NO/cGMP suppression Deteriorate Microcirculation via Pericyte Phenotype Transformation after Subarachnoid Hemorrhage in Rats

Abstract: Subarachnoid hemorrhage (SAH) usually results from ruptured aneurysm, but how leaked hemoglobin regulates the microcirculation in the pathophysiology of early brain injury after SAH is still unclear. In the present study, we sought to investigate the role and possible mechanism of hemoglobin induced pericyte phenotype transformation in the regulation of microcirculation after SAH. Endovascular perforation SAH rat model, brain slices and cultured pericytes were used, and intervened with endothelial nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
(70 reference statements)
5
27
0
Order By: Relevance
“…The preincubation of cells with l ‐NAME or SNAP did not affect invasion or intracellular bacterial growth, as observed in Figure E. To further investigate the phenomenon of inhibition of IL‐1β secretion mediated by NO, we infected BMDMs with B. abortus in the presence or absence of bovine hemoglobin (Hg), a widely known NO scavenger . These results strengthen our findings shown in the Figure , since the preincubation with Hg increased IL‐1β secretion and strongly reduced NO 2 − detection in B. abortus ‐infected cells (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 82%
“…The preincubation of cells with l ‐NAME or SNAP did not affect invasion or intracellular bacterial growth, as observed in Figure E. To further investigate the phenomenon of inhibition of IL‐1β secretion mediated by NO, we infected BMDMs with B. abortus in the presence or absence of bovine hemoglobin (Hg), a widely known NO scavenger . These results strengthen our findings shown in the Figure , since the preincubation with Hg increased IL‐1β secretion and strongly reduced NO 2 − detection in B. abortus ‐infected cells (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 82%
“…There are two kinds of brain pericytes, namely granular pericytes and filamentous pericytes, in microvessels under electron microscopy [35]. These two populations of pericytes can be distinguished by the presence of lysosome-like granules in the cytoplasm [36]. Granular pericytes, which compose about 95% of the entire cerebral pericyte population [36], may serve as scavenger cells in the brain.…”
Section: Physiological Functions Of Pericytes In the Normal Brainmentioning
confidence: 99%
“…These two populations of pericytes can be distinguished by the presence of lysosome-like granules in the cytoplasm [36]. Granular pericytes, which compose about 95% of the entire cerebral pericyte population [36], may serve as scavenger cells in the brain.…”
Section: Physiological Functions Of Pericytes In the Normal Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematoxylin and eosin staining showed that the inner elastic membrane appeared serrated and it was thickening in the basilar artery, which might be caused by the imbalance of vasoconstrictors and vasodilators. 8 NO is a diffusible factor and powerful vessel dilator, 30 which was suggested to reverse the effects of the ET-1-induced vasoconstriction. 7 In this study, SA administration increased the content of NO and decreased the concentration of ET-1.…”
Section: Intra-arterial Infusion Of Nimodipine or Nicardipine As Calcmentioning
confidence: 99%